Question
upstudy study bank question image url

A. If X and Y are random variables with joint density function \[ f(x, y)=\left\{\begin{array}{lll}4(x+y-3) & 0
Ask by Rodriguez Moran. in Nigeria
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The conditional expectation of \( X \) given \( Y \) is \( \frac{4(2y - \frac{10}{3})}{8y - 16} \).

Solution

To find the conditional expectation of \( X \) given \( Y \), we need to follow these steps: 1. **Find the marginal density function of \( Y \)**, \( f_Y(y) \). 2. **Find the conditional density function of \( X \) given \( Y \)**, \( f_{X|Y}(x|y) \). 3. **Calculate the conditional expectation \( E[X|Y=y] \)** using the conditional density function. ### Step 1: Find the marginal density function of \( Y \) The marginal density function of \( Y \) can be found by integrating the joint density function \( f(x, y) \) over the range of \( x \): \[ f_Y(y) = \int_{-\infty}^{\infty} f(x, y) \, dx = \int_0^2 f(x, y) \, dx \] Given the joint density function: \[ f(x, y) = 4(x+y-3) \quad \text{for } 0 < x < 2 \] We need to determine the limits for \( y \). The expression \( x + y - 3 > 0 \) implies \( y > 3 - x \). Since \( 0 < x < 2 \), we have: - When \( x = 0 \), \( y > 3 \) - When \( x = 2 \), \( y > 1 \) Thus, \( y \) must be in the range \( 1 < y < 3 \). Now we can compute \( f_Y(y) \): \[ f_Y(y) = \int_0^2 4(x+y-3) \, dx \] Calculating the integral: \[ = 4 \int_0^2 (x + y - 3) \, dx \] Calculating the integral: \[ = 4 \left[ \frac{x^2}{2} + yx - 3x \right]_0^2 \] Evaluating at the limits: \[ = 4 \left[ \frac{2^2}{2} + 2y - 6 \right] = 4 \left[ 2 + 2y - 6 \right] = 4(2y - 4) = 8y - 16 \] Thus, the marginal density function of \( Y \) is: \[ f_Y(y) = 8y - 16 \quad \text{for } 1 < y < 3 \] ### Step 2: Find the conditional density function of \( X \) given \( Y \) The conditional density function \( f_{X|Y}(x|y) \) is given by: \[ f_{X|Y}(x|y) = \frac{f(x, y)}{f_Y(y)} \] Substituting the values we found: \[ f_{X|Y}(x|y) = \frac{4(x+y-3)}{8y-16} \] ### Step 3: Calculate the conditional expectation \( E[X|Y=y] \) The conditional expectation \( E[X|Y=y] \) is given by: \[ E[X|Y=y] = \int_{-\infty}^{\infty} x f_{X|Y}(x|y) \, dx = \int_0^2 x \cdot \frac{4(x+y-3)}{8y-16} \, dx \] Calculating the integral: \[ = \frac{4}{8y-16} \int_0^2 x(x+y-3) \, dx \] Calculating the integral: \[ = \frac{4}{8y-16} \int_0^2 (x^2 + xy - 3x) \, dx \] Calculating each term: 1. \( \int_0^2 x^2 \, dx = \left[ \frac{x^3}{3} \right]_0^2 = \frac{8}{3} \) 2. \( \int_0^2 xy \, dx = y \left[ \frac{x^2}{2} \right]_0^2 = 2y \) 3. \( \int_0^2 3x \, dx = 3 \left[ \frac{x^2}{2} \right]_0^2 = 6 \) Putting it all together: \[ = \frac{4}{8y-16} \left( \frac{8}{3} + 2y - 6 \right) = \frac{4}{8y-16} \left( 2y - \frac{10}{3} \right) \] Thus, the conditional expectation \( E[X|Y=y] \) is: \[ E[X|Y=y] = \frac{4(2y - \frac{10}{3})}{8y - 16} \] This is the final expression for the conditional expectation of \( X \) given \( Y \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the conditional expectation of \( X \) given \( Y \), we first need the conditional density function of \( X \) given \( Y = y \). The conditional density is given by the formula: \[ f_{X|Y}(x|y) = \frac{f(x, y)}{f_Y(y)} \] where \( f_Y(y) \) is the marginal density of \( Y \). 1. **Finding the marginal density \( f_Y(y) \)**: We can find \( f_Y(y) \) by integrating the joint density function \( f(x, y) \) over the appropriate range for \( x \): \[ f_Y(y) = \int_{0}^{2} f(x,y) \, dx = \int_{0}^{2} 4(x+y-3) \, dx \] The limits for \( x \) are \( 0 \) to \( 2 \), since the joint density is supported in this region. Carrying out the integral: \[ f_Y(y) = 4 \int_{0}^{2} (x + y - 3) \, dx \] The integral simplifies as follows: \[ = 4 \left[ \frac{x^2}{2} + (y - 3)x \right]_{0}^{2} = 4 \left[ \frac{2^2}{2} + (y - 3)(2) \right] = 4 \left[ 2 + 2y - 6 \right] = 4(2y - 4) = 8y - 16 \] The marginal density has valid support \( y \) such that \( 0 < 2+y-3 < 0 \) leads to \( y < 1 \). 2. **Calculating \( f_{X|Y}(x|y) \)**: We plug \( f_Y(y) \) back into the conditional density formula: \[ f_{X|Y}(x|y) = \frac{4(x+y-3)}{8y - 16} \] 3. **Finding \( E[X|Y=y] \)**: To find the conditional expectation \( E[X|Y=y] \), we compute: \[ E[X|Y=y] = \int_{0}^{2} x f_{X|Y}(x|y) \, dx \] Substituting in \( f_{X|Y}(x|y) \): \[ E[X|Y=y] = \int_{0}^{2} x \cdot \frac{4(x+y-3)}{8y-16} \, dx \] This integral needs evaluation to find \( E[X|Y=y] \). 4. **Final integration and simplification** gives us \( E[X|Y=y] = \frac{y - 3 + 2}{2} \). Thus, the conditional expectation \( E[X|Y] \) is completed through these steps.

Related Questions

Latest Probability Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy